TRADITIONAL MEDICINE VALUE IN HIV/AIDS - Josiah, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The value of traditional medicine in HIV/AIDS is holistic therefore calls for attention and research that may lead to the cure of HIV not withstanding behaviour and nutrition. An anti viral plant even if it works on herpes simplex is beneficial to HIV/AIDS. Asparagus africana has the ability of utilizing oxygen in the body thus promoting deoxidation. The asparagosides in it are anti viral. Cadiospermum halicacabum is anti inflammatory, boosts immunity, is a histamine release inhibitor, fights diahorrhea and acts as a reverse transcriptase inhibitor with its cadiospermine in it. Then why not use it in HIV/AIDS? Gynopis yardarm is a vegetable, contains an anti viral diethytoluamide that makes it useful in HIV/AIDS. Methods: A cross sectional study in four different hospices was done in Eastern Cape for a period of more than one year. Results: A total of 75 patients were followed for over one year. CD4 count increased from 200cells/mms to 450cells/mms. Increament in body weight was noted from 49kgs to 64 kgs. Conclusion: Hibiscus sabdariffa is very useful in treatment of HIV/AIDS patients: It has the ability of removing deoxidation and It makes the sick regain euphoriant.References: 1. Monic Adrians- The medical gardens in the Rwenzori region 2. Jackie segyin-Eynad Home doctor 1994. 3. Medical plants in the tropical countries by German institute for medical mission 4. The Victoria basin researchers (inter university council).